Locus of control, coping flexibility, and post-migration growth among mainland Chinese university students in Macao. (November 2021) - Yang, Hong Mian; Li, Yun; Zhang, Meng Xuan; Tao, Vivienne Y.K.; Tong, Kwok Kit; Wu, Anise M.S.
Abstract: This study aimed to investigate if locus of control (LOC; including internal, external-powerful others, and external-chance) and coping flexibility were associated with post-migration growth (PMG) among sojourning students. Mainland Chinese university students ( N = 286 [68.5 % female]; Mage = 18.902, SD  = .748) in Macao completed three waves (Time 1 [T1], Time 2 [T2], and Time 3 [T3]) of survey across 2 years. Results of our path analysis showed that internal LOC (T1) was significantly correlated with higher levels of coping flexibility (T2) and PMG (T3). Moreover, findings of further mediation tests also indicated that coping flexibility partially mediated the positive influence of internal LOC on PMG. In the path model, the effects of both external-powerful others LOC and external-chance LOC on coping flexibility were not statistically significant but external-chance LOC exerted a significant negative direct effect on PMG. Our findings revealed the potential value of internal LOC and coping flexibility in facilitating intrapersonal and interpersonal growth when studying abroad, and their practical implications in promoting international students' successful adjustment to the host society were discussed.